Implementation of Islamic Business Ethics in Contemporary Culinary Business Practices (A Study on Mie Gacoan Tasikmalaya 1-Siliwangi ) - Resi Resliawati Resi; Rismawati Risma; Alfiyah Nur Azizah Alfiyah Nur Azizah; Aris Saepul Anwar Aris Saepul Anwar; Niningtyas Rahayuningsing Niningtyas Rahayuningsing; Asep Saepulloh Asep Saepulloh (ISTIFADA : Jurnal Ekonomi dan Lembaga Keuangan Syariah, 2026)
Implementation of Islamic business ethics in contemporary culinary business practices at Mie Gacoan Tasikmalaya 1-Siliwangi. Islamic business ethics is a set of moral values ​​derived from the Qur'an and Hadith that emphasize the principles of honesty ( ṣ iddiq ), trustworthiness ( amanah ), intelligence ( fa ṭ anah ), and communication ( tabligh ) in economic activities. This study uses a qualitative method with a field observation approach to identify the extent to which these values ​​are applied in business practices. It shows that the application of Islamic business principles at Mie Gacoan Tasikmalaya Siliwangi has implemented these principles, including through price transparency and product conformity with the information conveyed ( ṣ iddiq ), friendly service and responsibility in fulfilling orders ( amanah ), product innovation and marketing strategies that are adaptive to market needs ( fa ṭ anah ), and polite and effective communication with consumers ( tabligh ). The implementation of these values ​​contributes to building consumer trust and maintaining business sustainability